Application For Prediction Of The Spread Of The Covid-19 Outbreak In Manado - Vortuna, Vharadien Veronika; Jacobus, Agustinus; kambey, feisy diane (Universitas Sam Ratulangi, 2021)
Prediction system or system that predicts is a system that is used to predict something that will happen in the future or the future. Currently, the whole world, especially the city of Manado, is in a situation where the Covid-19 virus outbreak has paralyzed various aspects. Therefore, this study aims to provide information on predicting the spread of COVID-19 in Manado. Because this disease spreads to all corners of society easily, of course it requires information about the development of its spread in the future so that people can know the developments about the spread of the disease. The research entitled